THE OPPORTUNITIES THAT CURRENTLY UZBEKISTAN ARE OWNING FOR INCREASING ECOTOURISM: Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
Ecotourism has become a major tool for the rising environmental awareness of locals and visitors ensuring long-term sustainability. The tourists are becoming increasingly sophisticated in having meaningful travel experiences including communication with local people,learning their culture, observation of unique ecosystems, flora and fauna of the untouched areas. Uzbekistan's diverse ecology from mountains to deserts, from deserts to plains can support the country with the great ecotourism potential. Such opportunities can provide social, environmental and economic benefits to the country when it is comprehensively modified and meets international standards